2012
DOI: 10.1111/j.1475-097x.2012.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle force recovery in relation to muscle oxygenation

Abstract: The aim of this study was to investigate the relative contribution of human muscle reoxygenation on force recovery following a maximal voluntary contraction (MVC). Ten athletes (22·9 ± 4·0 years) executed a plantar-flexion sequence including two repeated MVCs [i.e. a 30-s MVC (MVC(30)) followed by a 10-s MVC (MVC(10))] separated by 10, 30, 60, 120 or 300 s of passive recovery. A 10-min passive recovery period was allowed between each MVC sequence. This procedure was randomly repeated with two different recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Other research has shown arterial occlusion to have no significant effect on muscleforce recovery in the plantar flexors. 22 In the same study, muscle oxygenation and force-production capacity were found to be only moderately correlated. This observation may have important ramifications when considering the effect of IPC on repeated-sprint ability, in so much as it may confer a benefit in sparing ATP while exerting no negative impact on force production.…”
Section: Discussionmentioning
confidence: 85%
“…Other research has shown arterial occlusion to have no significant effect on muscleforce recovery in the plantar flexors. 22 In the same study, muscle oxygenation and force-production capacity were found to be only moderately correlated. This observation may have important ramifications when considering the effect of IPC on repeated-sprint ability, in so much as it may confer a benefit in sparing ATP while exerting no negative impact on force production.…”
Section: Discussionmentioning
confidence: 85%
“…Muscle O 2 kinetics and PCr resynthesis are also tightly linked (Kime et al, 2003 ). A high perfusion and reoxygenation rate of the active musculature during recovery periods, assessed via near-infrared spectroscopy (NIRS), is paramount to reproduce a high performance in a subsequent bout (Ufland et al, 2012 ). The delivery of O 2 is also highly sensitive to manipulations of environmental O 2 and compromised at altitude, which may contribute to impairment during repeated-sprint exercise (Billaut and Buchheit, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study used a 2-wavelength, portable, continuous-wave NIRS system (Portamon, Artinis, Medical System, Zetten, Netherlands). The system utilized the modified Beer–Lambert and spatially resolved spectroscopy methods to measure changes in deoxyhemoglobin (HHb) and oxyhemoglobin (HbO 2 ) concentrations at 760 and 850 nm wavelengths ( Ufland, 2012 ; Ufland et al, 2012 ). Due to an overlap in wavelengths, myoglobin concentrations could not be separated from hemoglobin concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Each NIRS device had three fixed optode sets capable of penetrating 35 mm into the target tissue. A Portamon sensor was placed on the belly of the VL and medial forearm flexor muscles, primarily the flexor carpi radialis ( Ufland, 2012 ; Ufland et al, 2012 ). Each placement was measured, marked with permanent marker, and recorded during baseline testing to ensure placement consistency before each test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation